Segunung Goes Digital: Application of Virtual Tour to Kampung Adat Segunung - Alawi, A. Muammar; Setiyowati, Arin; Nuryananda, Praja Firdaus (Future Science, 2023)
Kampung Adat Segunung, is one of the fostered areas and the partners of the Faculty of Social and Political Sciences UPN